Природа динамiчного кросовера в ортотерфенiлi - Baran, J.; Davydova, N. A.; Drozd, M.; Ponezha, E. A.; Reznichenko, V. Ya. (Publishing house "Academperiodika", 2018)
We have conducted the infrared spectroscopic study and differential scanning calorimetry measurements (DSC) on orthoterphenyl (OTP), aiming to explore the physical nature of the dynamic crossover at 1.2Tg found in variety experiments on OTP. We have obtained that, at T ≤ 1.2Tg (∼290 K) in the supercooled liquid OTP, the crystal nuclei appear and are absent at higher temperatures. These results suggest that the origin of the dynamic crossover at 1.2Tg is related to the formation of fluctuating nuclei in the supercooled liquid, as a temperature of 1.2Tg is approached. Therefore, we would expect that the appearance of the nuclei would change the molecular dynamics from individual to cooperative.